An alternative GaSb substrate allowing close-spaced sublimation of Cd0.9Zn0.1Te epitaxial thick film for radiation detectors. (15th August 2022) - Li, Yang; Cao, Kun; Zha, Gangqiang; Zhang, Xinlei; Wan, Xin; Zhao, Dou; Liu, Yajie; Jie, Wanqi
Abstract: Cd0.9 Zn0.1 Te have been used for the high-performance room-temperature nuclear radiation detectors for decades. However, searching for more efficient growth methods of high-quality crystals is still an attractive research topic. This study proved the successful growth of high quality Cd0.9 Zn0.1 Te epitaxial thick films on GaSb (001) substrates using close-spaced sublimation method, where the lattice mismatch between GaSb and Cd0.9 Zn0.1 Te was −5.7%, much smaller than that between GaAs and Cd0.9 Zn0.1 Te (−13.9%). The interfacial mismatch dislocations on CdZnTe/GaSb heterojunctions were found to be much less than those of CdZnTe/GaAs, as confirmed by cross-sectional selected area electron diffraction patterns and high angle annular dark field images of transmission electron microscopy. Compared to Au/CdZnTe/GaAs, the FWHM of double crystal X-ray rocking curve and leakage current of Au/CdZnTe/GaSb detector were lower, and the resistivity and ( μ τ ) e were higher. The detector made from the as-grown CdZnTe/GaSb thick film was demonstrated to possess the energy resolution of 17% for 241 Am@59.54 KeV γ ray energy spectrum, indicated the potential application of GaSb as a suitable substrate for detector-grade CdZnTe film growth. Highlights: CdZnTe epitaxial thick films were successfully grown on GaSb substrates by close-spaced sublimation. Mismatch dislocations of CdZnTe/GaSb interface were found to be less than those of the CdZnTe/GaAs interface. Energy resolution of 17% was measured for Au/CdZnTe/GaSb radiation detector for 241 Am@59.5 keV γ ray.